Potentially zoonotic gastrointestinal nematodes co‐infecting free ranging non‐human primates in Kenyan urban centres. Issue 3 (5th January 2021) - Mbuthia, Peris; Murungi, Edwin; Owino, Vincent; Akinyi, Mercy; Eastwood, Gillian; Nyamota, Richard; Lekolool, Isaac; Jeneby, Maamun
Abstract: Background: Natural infections with soil‐transmitted nematodes occur in non‐human primates (NHPs) and have the potential to cross primate‐species boundaries and cause diseases of significant public health concern. Despite the presence of NHPs in most urban centres in Kenya, comprehensive studies on their gastrointestinal parasites are scant. Objective: Conduct a cross‐sectional survey to identify zoonotic nematodes in free‐ranging NHPs found within four selected urban and peri‐urban centres in Kenya. Methods: A total of 86 NHPs: 41 African green monkeys [AGMs] ( Chlorocebus aethiops ), 30 olive baboons ( Papio anubis ), 5 blue monkeys ( Cercopithecus mitis stuhlmanni ) and 10 red‐tailed monkeys ( Cercopithecus ascanius ) were sampled once in situ and released back to their habitat. Microscopy was used to identify nematodes egg and larvae stages in the samples. Subsequently, PCR coupled with high‐resolution melting (PCR‐HRM) analysis and sequencing were used to identify nodule worms. Results: NHPs inhabiting densely populated urban environs in Kenya were found infected with a rich diversity of nematodes including three potentially zoonotic nematodes including Oesophagostomum stephanostomum, Oesophagostomum bifurcum and Trichostrongylus colubriformis and co‐infections were common. Conclusion: Phylogenetic analysis showed that O. stephanostomum from red‐tailed and blue monkeys have a close evolutionary relatedness to human isolates suggesting the zoonotic potential of this parasite. Moreover, we also report the first natural co‐infection of O. bifurcum and O. stephanostomum in free‐ranging AGMs. Abstract : Free ranging NHPs in Kenyan urban centres are hosts to several zoonotic helminths including O. bifurcum and O. stephanostomum . Africa green monkeys (AGMs) co‐infection with Oesophagostomum spp. and Trichostrongylus species informs on potentially new reservoir hosts for the parasites in densely populated Kenyan towns. PCR coupled with high resolution melting (PCR‐HRM) enabled non‐subjective characterization of O. bifurcum and O. stephanostomum . It efficiently differentiated between the two nodular worm species thus greatly reducing the cost of sequencing and enabling rapid nematode identification.